Self-Nanomicellar Dispersion of Rosuvastatin for Improved Bioavailability: Formulation, Optimization and Pharmacokinetic Studies - Gowripattapu, Sridevi; Dinakaran, SathisKumar; Subramanian, Selvamuthukumar (Indian Journal of Pharmaceutical Education and Research, 2024)
Introduction: Rosuvastatin is a statin drug used to lower cholesterol, but it has poor water solubility and low bioavailability, limiting how effective it can be. The objective of the present study was to formulate and evaluate a SNEDDS “self-nano emulsifying drug delivery systems” of Rosuvastatin and to optimize its formulation. Materials and Methods: The SNEDDS was produced using Egg lecithin, Capmul MCM, and Tween 20 as co-surfactant, oil, and surfactant, respectively. The formulation was optimized by Design Expert 12 and was characterized by various techniques such as globule size, zeta potential, % transmittance, refractive index, drug release studies etc. The optimized SNEDDS was loaded with different adsorbents by adsorption using technique and characterized for in vitro release studies, in vivo drug release studies and comparison studies with pure drug. Results: The SNEDDS were optimized which shows a negative zeta potential of -4.32, a globule size of 42.21 nm, and a faster release compared to other formulations. Drug release studies (in vitro) showed that the optimized SNEDDS-loaded tablet had more rapid rate of drug release (99.9% at 40 min) when compared with the pure drug (36.73% at 40 min). The in vivo study in healthy rabbits showed a highest release rate of drug from the SNEDDS loaded tablet (RRSV1) when compared with the pure drug resulting in an enhanced bioavailability of Rosuvastatin. Conclusion: The study concludes that the SNEDDS of Rosuvastatin is a promising approach for increasing solubility, rate of dissolution and bioavailability.
Keywords: Rosuvastatin; SNEDDS; Statistical optimization; Solubility; Dissolution rate; Bioavailability